Studies of mortuary value system and its behavior: Columbarium Niche burial and natural burial as study cases in Taiwan - KUO-CHU YANG; HSIAO-PING HUNG; FU-CHUAN HSU; YIN-AN CHEN (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: This research aims to examine the contemporary Taiwanese mortuary practices, identifies the disconnect between the country’s mortuary value system and its actual practice, and delves into the connections between the two and grief support. The government of Taiwan’s research findings will be used as a basis for developing funeral policy. Method: Secondary data analysis, in-depth interviews, and thematic data analysis were used to compile this report. Participants in this study were relatives who have suffered a recent death within the last three years. In total, there are thirteen people taking part. 8 people chose to be interred in a columbarium niche, while 5 people went the natural route. Findings: Lineal relatives are the backbone of the funeral planning strategy; "to be environmentally friendly and sanitation" and "not to be troublesome to the bereaved" are the primary justifications for selecting burial methods. Traditional wiping and bathing rites seem to be losing their fundamental purpose as more and more people choose not to send obituaries and shorten the length of the funeral to just seven days. While there is a discrepancy between funeral costs and etiquette, it is detrimental to grief care. Implications/Novel Contribution: The findings of this study will be used by the government of Taiwan to guide the creation of a policy regarding natural burials. Grief support for the deceased’s family must be balanced against the government’s broader goal of protecting the environment and improving public health. Moreover, this study aims to bring the attention of the funeral industry, academic institutions, and policymakers to the negative impact of mortuary arrangements on the condensing of time and space.